Canon Law and Christian Societies between Christianity and Islam - Maser, Matthias; Lorenzo Jiménez, Jesús; Martin, Geoffrey K. (Brepols, 2024)
The unique Arabic version of the Iberian canon law code 'Collectio Hispana', preserved in a mid-eleventh-century manuscript of the Royal Library of El Escorial, has been deemed “the most distinguished and characteristic” work of medieval Andalusi Christian writing. It represents an exceptional source witness to the internal legal organisation of Christian communities in Muslim-dominated al-Andalus as well as to their acculturation to Islamicate environments. Yet, the Arabic collection has received only little scholarly attention so far. This volume presents the results of a recent interdisciplinary research project on the Arabic canon law manuscript, flanked by contributions from neigbouring fields of research that allow for a comparative assessment of the substantial new findings. The individual chapters in this volume address issues such as the origins of the Arabic law code and its sole transmitting manuscript, its language and translation strategies, its source value for both the persistence and transformation of ecclesiastical institutions after the Muslim conquest, or the law code's position in the judicial practice of al-Andalus. The volume brings together the scholarly expertise of distinguished specialists in a broad range of disciplines, e.g. history, Arabic and Latin philology, medieval palaeography and codicology, archaeology, coptology, theology and history of law.